Speciation of Enterococcus species: better way to deal with clinical infections at resource limited settings - Patel, Kinjal P.; Mulla, Summaiya (International Journal of Research in Medical Sciences, 2020)
Background: Enterococcus species are well known for its intrinsic resistance pattern to several antibiotics. Hence, appropriate management and prevention is essential in any healthcare facility. Present study was conducted to establish an accessible biochemical tests to differentiate Enterococcus species at resource limited settings. Methods: Enterococci isolated from various clinical specimens were speciated using an array of biochemical reactions and antimicrobial susceptibility testing was performed by Kirby-Bauer disc diffusion method. Results were interpreted as per Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Out of 107 enterococcal isolates, 63(59%) were E. faecium, 40(37%) were E. fecalis, 2(2%) were E. hirae, 1(0.9%) was E. raffinosus and 1(0.9%) was E. gallinarum. E. faecium and E. fecalis showed 23% and 7% vancomycin resistance respectively, while E. gallinarum showed low level vancomycin resistance. Conclusions: Enterococcus speciation can be done using simple biochemical reactions and its susceptibility pattern enables to distinguish Van phenotypes too. Hence, it is helpful for management of infections in resource limited settings to a greater extent.